Fermentation Timing Effect on Main Plant Nutrients in Liquid Biofertilizers from Fish, Prawn and Golden Applesnail Wastes - VONGDETH, Kingsadingthongkham (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Currently, there are various outsell of biofertilizers, but the difference of quality or efficiency of biofertilizers for plants depends on the process such as choosing raw materials, fermented timing, contamination, and production process. In this case study, we were made 3 types of liquid biofertilizers producing with different 3 types of raw materials such as: fish, prawn and golden applesnail wastes to ferment with molasses in a 1:2 ratio, we were separated the fermenting into 3 periods of time: 15 days, 30 days and 45 days, after that we bring the liquid biofertilizers to determination of three macronutrients: total nitrogen, phosphorus and potassium. The study found that the pH levels were between 5.00-5.60; the main macronutrient elements as a percentage of the weight per volume (%w/v) we found the value of liquid biofertilizers as following: total nitrogen was 0.28-0.79%; phosphorus was 0.30-0.27% and potassium was 0.51-0.63%. The quantity of nitrogen and phosphorus in liquid biofertilizers that ferment for 30 days has higher than 15 days and 45 days respectively. The quantity of potassium from fish wastes and golden applesnail wastes that fermented 45 days has higher than 30 days and 15 days respectively. Nitrogen and phosphorus in liquid biofertilizers from prawn wastes > fish wastes > golden applesnail wastes; for potassium in liquid biofertilizers from golden applesnail wastes > fish wastes > prawn wastes.